1995
DOI: 10.1007/bf00410188
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Cl? current and physiological roles of the intestinal c-kit-positive cells

Abstract: Chronic injection of an anti-c-KIT receptor tyrosine kinase monoclonal antibody (ACK2) results in the disruption of the normal motility patterns of young BALB/c mice intestine. This effect is accompanied by a drastic decrease in the number of intestinal c-kit-expressing (c-kit+) cells when studied immunohistochemically with the fluorescence-labelled antibody. In order to clarify the mechanism underlying the ACK2 action and the physiological roles of intestinal c-kit+ cells, we studied the excitability of intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 40 publications
2
77
1
Order By: Relevance
“…One report suggested that ICCs from the murine small intestine generated spontaneous Ca 2+ -activated Cl -currents (Tokutomi et al, 1995). This conclusion was based on pharmacological tests using a Cl -channel-blocking drug (4-acetoamido-4-isothiocyanat-ostilbene-2,2-disulphonic acid; SITS).…”
Section: Possible Mechanisms For the Pacemaker Activity In Interstitimentioning
confidence: 99%
“…One report suggested that ICCs from the murine small intestine generated spontaneous Ca 2+ -activated Cl -currents (Tokutomi et al, 1995). This conclusion was based on pharmacological tests using a Cl -channel-blocking drug (4-acetoamido-4-isothiocyanat-ostilbene-2,2-disulphonic acid; SITS).…”
Section: Possible Mechanisms For the Pacemaker Activity In Interstitimentioning
confidence: 99%
“…As colonic smooth muscle cell has only the high-threshold Ca-channels which are sensitive to organic Ca-antagonists [31], the pacemaker potential of the ICC is assumed to be produced by a sustained inward current carried through the low-threshold Ca-channels, analogous to pacemaker potentials in cardiac muscle. However, cultured ICC of the mouse intestine produce spontaneous membrane potential changes through opening Ca-activated Cl-channels [32]. The processes for the generation of spontaneous activity are suggested to be as follows: Ca 2ϩ released from internal stores activates Cl-channels to depolarize the membrane and, when the potential exceeds the threshold level, opens L-type Ca-channels to form a large depolarization.…”
Section: Spontaneous Activity Of Intestinal Smooth Musclesmentioning
confidence: 99%
“…Furthermore, spontaneous inward currents are detected in isolated ICC, but not in gastrointestinal smooth muscle cells, when they are both maintained under cell culture conditions (Koh et al, 2002). The cellular mechanisms involved in this spontaneous activity in gastrointestinal tissues remain unclear, but are likely to involve cationic (Koh et al, 2001(Koh et al, , 2002, and/or Cl currents (Tokutomi et al, 1995;Huizinga et al, 2002). The spontaneous activity is not inhibited by several-type of organic Ca 2+ -antagonists such as verapamil (Golenhofen and Lammel, 1972), diltiazem (Ishikawa et al, 1985) and nifedipine (Dickens et al, 1999;Ishikawa et al, 2004;Liu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%